Tinjauan Asas Demokrasi Ekonomi Atas Penyalahgunaan Posisi Dominan Dalam Membatasi Pengembang Teknologi Di Era Industri Kreatif : Studi Atas Tarif Layanan Google Play Store - Djaka, Meriyanti (Jurnal Hukum & Pembangunan, 2023)
National economic development in the creative industry era really requires community participation in utilizing technology, one of which is by developing digital application technology. Distribution of digital applications is generally marketed through the Google Play Store because of its very high market share in Indonesia. In marketing their products, technology developers charge a service fee of around 15-30% of in-app purchase sales for the applications they develop. This research aims to prove the abuse of a dominant position by companies distributing digital applications through the Google Play Store which limits technology developers, as well as reviewing this with the principles of economic democracy that exist in Indonesia. The results of this research prove that companies distributing digital applications through the Google Play Store have abused their dominant position by restricting technology developers by making exclusive agreements and increasing Google Play billing service rates. This abuse of a dominant position is not in accordance with the principles of Indonesian economic democracy which prohibits actions that are destructive, deadly, hindering and detrimental to human creativity, especially the Indonesian people, both consumers and producers.